SUN-497 Atypical Parathyroid Adenoma- Is There More Than What Meets the Eye ? - Mayorga, Mabel (J Endocr Soc, 2019)
Background: Parathyroid adenoma with severe hyperparathyroidism and parathyroid carcinoma can have similar clinical presentations. Atypical cases should prompt suspicion for parathyroid carcinoma. We report such a case of an atypical parathyroid adenoma in a young woman. Case: A 22 year old woman without any past medical history presented with an inability to bear weight on her left leg after ascending stairs. X-rays showed lytic lesions of the left femur and pubic ramus, and an intertrochanteric fracture of the left femur. Suspicion for a pathologic fracture prompted further imaging. CT imaging demonstrated an asymmetric enlarged mass originating from the inferior aspect of the right thyroid lobe and bilateral medullary nephrocalcinosis. MRI showed a pathologic fracture with multiloculated cystic lesions with multiple fluid levels in the left femur and multiple solid lesions in bilateral pubic rami. Labs: corrected calcium 14.9 mg/dL, phosphorus 1.8 mg/dL, ALP 208 U/L, PTH 1450.0 pg/mL, 25-hydroxy vitamin D 29 ng/mL, and creatinine 0.90 mg/dL. Endocrinology was consulted for management of hypercalcemia. Patient was managed with aggressive IV hydration, sq calcitonin, and a dose of IV pamidronate. The possibility of metastatic disease prompted a biopsy of the right pubic ramus, which demonstrated interstitial hemorrhage and numerous giant cells consistent with osteitis fibrosa cystica. A sestamibi scan revealed uptake suggestive of a large right parathyroid adenoma (measuring 3.0 x 2.7 x 5.7 cm) that corresponded to the mass found on CT. She underwent an ORIF of the left femur and right parathyroidectomy with resection of adjacent paratracheal lymph nodes after her calcium levels stabilized. The parathyroid mass was grossly described as being a well-circumscribed, well-encapsulated, yellow-tan, hemorrhagic lesion measuring 3.0 x 2.0 x 5.0 cm. Biopsy of the mass also indicated that the tumor was encapsulated and comprised of monotonous parathyroid cells without increase in mitosis. The final diagnosis was an atypical parathyroid adenoma. Post surgery, calcitriol and calcium supplements were initiated. Her PTH decreased to 19.3 pg/mL upon discharge from the hospital. Conclusion: This is an unusual presentation of severe hypercalcemia in a young woman due to primary hyperparathyroidism. Concerning features for possible parathyroid carcinoma included the patient’s young age, a corrected calcium level >14 mg/dL, a markedly elevated PTH, a parathyroid mass >3 cm, and the combination of renal and bone involvement.(1) These factors prompted the resection of adjacent lymph nodes with the parathyroid mass. Pathology was suggestive of an atypical parathyroid adenoma. These aggressive clinical features warrant close Endocrine follow up. 1. Marcocci C, Cetani F, Rubin MR, Silverberg SJ, Pinchera A, Bilezikian JP. Parathyroid carcinoma. J Bone Miner Res. 2008;23(12):1869-80.